Potret Adversity Quotient pada Mahasiswa Bimbingan Konseling Islam - Desika Nanda Nurvita (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
This study aims to obtain a description of the condition of adversity quotient among college students of Bimbingan Konseling Islam (BKI). This study uses a quantitative approach to the type of descriptive research. The sample in this study amounted to 93 college students of BKI IAIN Tulungagung. The sample taken by using simple random sampling technique. The data collection instrument used for this study using Adversity Quotient inventory and data analysis is done by using standard deviation and mean. The results showed that the adversity quotient levels among collage students of BKI is in high category 35.48%, medium category 53.76%, anda low category 10.75%.